NOTE:- i^(2n) = (i^2)^n = (-1)^n ; where n = natural number

Thus i^2 = -1 & i^3 = -1*i = -i

Hence 2i^2 + 3i^3 = (2*-1) + (3*-i) = -2 - 3i

2i^2 + 3i^3

i raised to the 2 power is -1.

2 (-1) +3i^3

Multiply 2 by -1 to get -2.

-2 +3i^3

i raised to the 3 power is -i.

-2 + 3(-i)

Multiply 3 by -i to get -3i.

-2-3i

**2i^2+3i^3 simplified is equivalent to -2-3i**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.

**Further Reading**